Physico-chemical characterization of starches extracted from potatoes of the group Phureja - Caceres, M; Mestres, C.; Pons, B; Gilbert, O.; Amoros, W.; Salas, E.; Dufour, Dominique; Bonierbale, Merideth W.; Pallet, D (Wiley, 2012)
Starch was extracted from twenty-four accessions of Group Phureja cultivated diploid potatoes, and from two commercial potato (Solanum tuberosum) varieties. Extracted starch samples were characterized and compared to industrial potato starch. Starch from Phureja generally exhibited smaller granule sizes and lower phosphorus content than starch from commercial potatoes. Amylose content and thermal properties (gelatinization temperature and enthalpy) were however in the same range for both groups. Starches from Phureja displayed very distinct pasting behavior from that of commercial potato. The former exhibited lower initial pasting viscosity but higher shear resistance. This may be related to lower starch granule size, causing lower swelling power and solubility. Iodine complexation results seem to indicate that phureja potatoes have higher proportion of amylopectin long chains. Phureja thus appears to be a promising new source of starch with specific physico-chemical and functional properties intermediate between industrial potato and cereal starches.